\(x^2-6x+16\)
\(=x^2+2x-8x-16\)
\(=x^2+2x-\left(8x+16\right)\)
\(=x\left(x+2\right)-8\left(x+2\right)\)
\(=\left(x-8\right)\left(x+2\right)\)
Đúng 0
Bình luận (0)
\(x^2-6x+16\)
\(=x^2+2x-8x-16\)
\(=x^2+2x-\left(8x+16\right)\)
\(=x\left(x+2\right)-8\left(x+2\right)\)
\(=\left(x-8\right)\left(x+2\right)\)
6x^2+5x+1
phan tich da thuc thanh nhan tu
Phan tich da thuc sau thanh nhan tu
6x^3+x^2+x+1
Phan tich da thuc thanh nhan tu
( x^2-6x+ 8)( x^2-8x +15) +1
phan tich da thuc sau thanh nhan tu
6x^3+x^2+x+1
Phan tich da thuc thanh nhan tu
(X^2-6x+8)(x^2-8x+15)+1
phan tich da thuc sau thanh nhan tu : x^4 - 6x^3 + 54x - 81
Phan tich da thuc thanh nhan tu
x3-6x2-x+30
phan tich da thuc thanh nhan tu :
5x^2 + 5xy - x - y
7x - 6x^2 - 2
phan tich da thuc thanh nhan tu
6x2 - 3xy + x + y -1